Potentials of Neuropeptides as Therapeutic Agents for Neurological Diseases - Xin Yi Yeo; Grace Cunliffe; Roger C. Ho; Su Seong Lee; Sangyong Jung (Biomedicines, 2022)
Despite recent leaps in modern medicine, progress in the treatment of neurological diseases remains slow. The near impermeable blood-brain barrier (BBB) that prevents the entry of therapeutics into the brain, and the complexity of neurological processes, limits the specificity of potential therapeutics. Moreover, a lack of etiological understanding and the irreversible nature of neurological conditions have resulted in low tolerability and high failure rates towards existing small molecule-based treatments. Neuropeptides, which are small proteinaceous molecules produced by the body, either in the nervous system or the peripheral organs, modulate neurological function. Although peptide-based therapeutics originated from the treatment of metabolic diseases in the 1920s, the adoption and development of peptide drugs for neurological conditions are relatively recent. In this review, we examine the natural roles of neuropeptides in the modulation of neurological function and the development of neurological disorders. Furthermore, we highlight the potential of these proteinaceous molecules in filling gaps in current therapeutics.